Nephrotoxicity of targeted therapy used to treat lung cancer - Li, Qiuling; Lin, Jieshan; Hao, Guojun; Xie, Aihua; Liu, Shuangxin; Tang, Bin (Frontiers in Immunology, 2024)
Lung cancer is the leading cause of cancer-related death worldwide, especially non-small cell lung cancer. Early diagnosis and better treatment choices have already provided a more promising prognosis for cancer patients. In targeted therapy, antagonists target specific genes supporting cancer growth, proliferation and metastasis. With the incorporation of targeted therapies in routine cancer therapy, it is imperative that the array of toxicities associated with these agents must be wellrecognized and managed, especially since these toxicities are distinct from those seen with conventional cytotoxic agents. Drug-related nephrotoxicity has attracted attention when initiating cancer therapy. Our review aims to summarize the adverse renal effects caused by targeted therapy during lung cancer treatment, mainly focusing on EGFR and ALK tyrosine kinase inhibitors. Also, we discuss the possible mechanism of the side effect and provide managements to help improve the renal function in clinical practice.